Market sense-making in design practice: exploring curiosity, creativity and courage. Issue 3 (12th February 2017) - Windahl, Charlotta
ABSTRACT: This paper introduces the three interrelated design catalysts of curiosity, creativity and courage, and explores how they actuate market sense-making activities in design practice. Drawing on the interplay between action and meaning dimensions in design practice and service-marketing theory, it specifically investigates when desirability, rather than feasibility or viability, is the locus of innovation activities. Thus, the following three aspects of market sense-making in design practice are identified: (a) curiosity catalyses empathy and the deep understanding of markets, which are seen as socially constructed of individual (value-in-use) and connected (value-in-context) experiences; (b) creativity catalyses 'logical leaps' with regard to understanding the opportunities for creating future markets; and (c) courage catalyses learning through iterations, which reduce cognitive bias with regard to market assumptions, thereby reducing cognitive bias in both curiosity- and creativity-driven activities.